The Impact of Mobile-Assisted Language Learning (MALL) on Students’ Vocabulary Mastery - Agustiah, Raiyan Ayu; Mariyani, Husna; Khotimah, Rani Nurul (Lembaga Penelitian dan Pendidikan Mandala, 2025)
In an increasingly mobile and connected world, integrating mobile-assisted language learning (MALL) into English vocabulary instruction offers promising avenues for enhancing learners’ lexical competence. This study investigates the effect of MALL on students’ vocabulary mastery in an EFL (English as a Foreign Language) context. A quasi-experimental design was employed with 60 secondary school students divided into experimental (MALL) and control (traditional instruction) groups. Vocabulary pre-test and post-tests were administered. Additionally, questionnaire data on learner attitudes and self-regulatory capacity were collected. Results indicated that the MALL group significantly outperformed the control group in vocabulary gains. Learners reported higher motivation, autonomy, and perceived utility of mobile tools. Implications for teaching practice and suggestions for further research are discussed.